2015
DOI: 10.1016/j.jma.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Processing, microstructure and mechanical properties of bimodal size SiCp reinforced AZ31B magnesium matrix composites

Abstract: The bimodal size SiC particulates (SiCp) reinforced magnesium matrix composites with different ratios of micron SiCp and nano SiCp (MSiCp:N-SiCp ¼ 14.5:0.5, 14:1, and 13.5:1.5) were prepared by semisolid stirring assisted ultrasonic vibration method. The AZ31B alloy and all as-cast SiCp/AZ31B composites were extruded at 350 C with the ratio of 12:1. Microstructural characterization of the extruded M14 þ N1 (MSiCp:N-SiCp ¼ 14:1) composite revealed the uniform distribution of bimodal size SiCp and significant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[ 13,14 ] The probability of AZ series alloys for biomedical application has been widely studied both in vitro and in vivo conditions. [ 15–18 ] However, excess intake of Al element may cause negative effects in organism, and high concentration of Al 3+ in the body enhances the risk of Alzheimer's disease. [ 19 ] Compared with other AZ alloys, AZ31 alloy, with low Al content, good mechanical properties, and corrosion resistance, is more suitable for acting as biodegradable material.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13,14 ] The probability of AZ series alloys for biomedical application has been widely studied both in vitro and in vivo conditions. [ 15–18 ] However, excess intake of Al element may cause negative effects in organism, and high concentration of Al 3+ in the body enhances the risk of Alzheimer's disease. [ 19 ] Compared with other AZ alloys, AZ31 alloy, with low Al content, good mechanical properties, and corrosion resistance, is more suitable for acting as biodegradable material.…”
Section: Introductionmentioning
confidence: 99%
“…Chin [ 27 ], Ho [ 28 ], Kwasniak [ 29 ], etc., show that the addition of copper (Cu), nickel (Ni), molybdenum (Mo) and titanium (Ti) can effectively improve the strength and ductility of the composite material [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, Cu and Ni form intermetallic compounds Mg 2 Cu [ 35 ] and Mg 2 Ni [ 36 ] with Mg, which hinder the ductility of magnesium-based composites [ 28 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in particle size will lead to an increase in the strain gradient in the matrix, resulting in an increase in dislocation and an improvement in the comprehensive mechanical properties of the composite. Numerous studies have shown that the interfacial bonding between the enhancer and the Mg matrix greatly affects the final mechanical properties of the material [ 48 , 49 , 50 ], and increasing the contact area between the reinforcement and the matrix is obviously beneficial to the interfacial bonding [ 32 ]. Ye [ 23 ] prepared Ti/AZ31 magnesium matrix composites with micron Ti particles as reinforcements, and the addition of Ti particles realized the bidirectional improvement of the strength and ductility of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Magnesium-based materials are approximately 35, 62 and 78% lighter than aluminium, titanium and steel, respectively, and thus promise significant weight savings. [6][7][8] Accordingly, they have been actively looked into by many engineering sectors such as automobiles and aerospace primarily for reducing component weight for realising fuel efficiency. 9,10 Researchers around the globe have used many ways to alter the mechanical properties of magnesium through alloying with different elements or making composites by reinforcing magnesium with hard-particles in micron or nanolength scales or applying advanced processing techniques such as powder metallurgy, high-pressure die casting, vacuum die casting, forming and equal channel angular processing.…”
Section: Introductionmentioning
confidence: 99%
“…35 Magnesium-based materials are approximately 35, 62 and 78% lighter than aluminium, titanium and steel, respectively, and thus promise significant weight savings. 68 Accordingly, they have been actively looked into by many engineering sectors such as automobiles and aerospace primarily for reducing component weight for realising fuel efficiency. 9,10…”
Section: Introductionmentioning
confidence: 99%